Fihrisü’l-mahtûtât. - Merkezü'l-Melik Faysal li'l-Buhûs ve'd-Dirâsâti'l-İslâmiyye. (Riyad)
6 cilt (1. c. 171 sayfa ; 2. c. 266 sayfa ; 3. c. 299, [21] sayfa ; 4. c. 267 sayfa ; 5. c. 274 sayfa ; 6. c. 300, [16] sayfa)